(untitled) - BAYU NIRWANA, LUHUR (RETAIN : Journal of Research in English Language Teaching, 2014)
The Implementation of Gap Information Activity to Teach Speaking Procedure Text to the Ninth Graders Luhur Bayu Nirwana 092084002 English Education, Faculty of Language and Art, State University of Surabaya luhurnirwana@gmail.com Dosen Pembimbing: Him’mawan Adi Nugroho, S.Pd., M.Pd. English Department, Faculty of Language and Art, State University of Surabaya Abstrak Bahasa Inggris adalah salah satu pelajaran wajib yang dimasukkan ke dalam kurikulum sekolah SMP dan SMA. Ini berarti siswa telah belajar bahasa sejak tahun pertama di bangku SMP. Tapi kemudian ketika mereka lulus dari sekolah tinggi kemampuan mereka berbahasa Inggris tidak berkembang dengan baik. Strategi mengajar tampaknya menjadi salah satu faktor kegagalan. Kegiatan kesenjangan informasi tampaknya menjadi pilihan bagi guru dalam melakukan kegiatan mengajar kepada siswa. Berdasarkan pandangan CLT kegiatan ini sangat membantu untuk mengembangkan keterampilan berbicara siswa. Ini memberikan siswa banyak kesempatan untuk berlatih berbicara selama kegiatan pembelajaran. Dengan demikian, peneliti memutuskan untuk melakukan penelitian tentang kegiatan ini untuk digunakan dalam mengajar berbicara teks prosedur untuk anak kelas sembilan. Ada dua pertanyaan penelitian dalam penelitian ini. Pertama adalah tentang pelaksanaan kegiatan informasi kesenjangan dalam mengajar berbicara teks prosedur untuk anak kelas sembilan. Yang kedua adalah tentang respon siswa terhadap implementasi dalam mengajar berbicara teks prosedur untuk anak kelas sembilan. Penelitian ini dilakukan di SMP Negeri 1 Bangkalan. Subyek adalah siswa IX-D nilai. Ini adalah penelitian deskriptif yang menggambarkan pelaksanaan kegiatan informasi gap untuk mengajar berbicara prosedur teks untuk siswa kelas sembilan. Berdasarkan hasil penelitian, pelaksanaan kegiatan informasi gap yang baik untuk diterapkan di kelas untuk mengajar berbahasa Inggris. Selain itu, siswa juga memberikan respon yang positif terhadap penerapan Gap Information Activity di dalam kelas. Kata Kunci: Gap Information Activity, Pengajaran Berbicara, Prosedur Teks, Kelas IX Abstract English is one of compulsory lessons which is put in junior and senior high school curriculum. It means students have learned the language since the first year in junior high school. But then when they are graduated from high school their English speaking ability does not develop well. The strategy seems to be one factor of the failure. The gap information activity seems to be an option for teacher in conducting teaching activity to students. Based on the CLT view this activity is helpful to develop students’ speaking skill. It gives students a lot of chances to practice speaking during the lesson activity. Thus, the researcher decides to conduct research about this activity to be used in teaching speaking procedure text to ninth graders. There are two research questions in this research. First is about the implementation of gap information activity in teaching speaking procedure text to ninth graders. The second is about students’ response toward the implementation in teaching speaking procedure text to ninth graders. This research was conducted in SMP Negeri 1 Bangkalan. The subject was the students of IX-D grades. It is the descriptive research which describes the implementation of gap information activity to teach speaking procedure text to ninth graders. Based on the result of the research, the implementation of gap information activity is good to be applied in class to teach speaking English. Moreover the students gave positive response toward the implementation of the activity. Keywords: Gap Information, Teaching Speaking, Procedure Text, Ninth Graders. INTRODUCTION Background of Study There is no objection that language and human being cannot be separated. Language is a media for people to communicate each other. Without language we cannot make a good interaction with other people. It is like what Yule (2010) says that human language trully serves a communication system in any situation. Moreover language also tool for learning, Yule (2010) states in his book that we can use language as a tool to learn about language itself. English has taken its role to be an international language. As quoted by Crystal in Cahyono & Widiati (2004) it is abudantly clear that now English has achieved its global status and the global status of English cannot be separated from its popular role as the language, science and technology. As the result of this situation, English has started being popular to be the media of communication among people around the world including Indonesian. As a country that wants to take a role in the world trading and competition, Indonesian government puts English as compulsory lesson in junior and senior high school curriculums. It is stated in Depdiknas (2006) that the aim of English teaching is to enable students to communicate with target language. In the term of communication, speaking skill takes the bigest role. However the final target of learning a certain language is to use it as a media to communnicate with other. Here in Indonesia, students start to learn English from the first year of Junior High School and it is continued regularly until they graduate from senior high school. But then the problem appears here. Although they have started to learn English since first year in Junior High School, their English skill do not develop well. There are seceral factors cause this failure, one of those factors is the method that is applied in class. Most of English teachers in Indonesia still apply teacher-centered class setting in teaching English. This class setting does not optimally give students chance to communicate through target language. This class setting will also provide low students talking time, so that the researcher will conduct a research of The Implementation of Gap Information Activity to Teach Speaking Procedure Text to Ninth Graders. The researcher decides to carry out research in speaking field because the main purpose of learning a language is to communicate and the most obvious way of human being to communicate is by speaking. Speaking is an important part of learning to speak the language teaching purposes should improve the communication skills of students, because that way, students can express themselves and learn how to follow the rules of social and cultural right in communicative circumtance. Kayi (2006) It makes speaking takes very important role in either learning or teaching English. The purpose of the students who learn language is to communicate. Finally it only can be communicated as well as expressed through speaking. Moreover students need a motivation to stimulate their willingness to communicate. They need a reason and an environment that supports and encourages them to start speaking through target language, English. Here is where teachers take their roles. Teachers have to be able to motivate their students to speak through English by creating the atmosphere and environment that support their students to speak and communicate through the target language, English. How then teachers will provide all those thing to students? It is of course they should find the right method to be applied in the class. Communicative Language Teaching (CLT) method can be a solution in this case. Richards (1999) says that CLT sees the needs of language teaching is to communicate each other in the real life. That is why the teacher should focus on communicative profiency rather than mastery of structures. There are some class activities that include in CLT, such as Role-play, interviews, information gap, pair-work and learning by teaching. Based on the perspective view of CLT, researcher decides to conduct a research about the implementatioan of Gap Information activity. It is because the gap of the information will make students curious and it gives the students reason to ask. Whenever they have a question to ask, it means they have reason to communicate and it can be good beginning for teacher to start teaching their students to communicate through target language. Moreover there are some genres in our national curriculum. They are procedure, descriptive, recount, narrative, report, news item, analytical exposition, hortatory exposition, spoof, explanation, discussion and review. The researcher will only concern on the procedure text because he believes it motivates students more since through procedure text students will be abble to share their idea of making or doing something. Based on the background study above, the researcher formulates questions in carrying out this study.Those questions are: (1) How is the implementation of gap information activity to teach speaking procedure text to ninth graders? (2) How is the students’ response of the implementation of gap information activity to teach speaking procedure text to ninth graders? This research will only focus on students’ speaking skill. It will be conducted to the ninth graders students in SMP Negeri 1 Bangkalan. The result of this research may not be the same with other school, other material and other students in different level Review Literature The aim for someone who learns language is in order to communicate with others using the target language. According to Harmer (2003) in order to make the communication to be successful, the speaker must have to structure the discourse in such a way that can be understood by the listeners. It means that when the speakers try to speak, they do not need to use complicated structure of discourse. They only need to make what they want to deliver can be understood by the listeners, so that the goal of communication can be achieved. Still related to the former, Kayi (2006) explains that the ability to communicate in a second language clearly and efficiently contributes to the success of the learners in school and success later in every phase of life. Kayi mentions the words “success” and “ability to communicate” in his statements. It is clearly enough that by being able to communicate well, people have a big chance to be successful in various situations. People tend to express what they feel through spoken language. If those people can express it well and understandable, they have more opportunity to get the things they want. In the country which uses English as foreign language like in Indonesia, most of its learners study language at school. They learn English with many limitations, such as limitation of time, place and situation, especially when they want to start learning speaking. They do not have enough opportunity to do that. Klancar (2006) states young learners in the communicative classroom should get as many speaking opportunities as possible and their speaking time should slowly but steadily rise so as to prepare them for various communicative situations. The opportunity of speaking will affect to the speaking ability. After giving the learners opportunity to speak teachers should improve learners’ speaking skill. At this point, the role of the English teacher is also important to the students’ speaking skill development. The teacher should be able to conduct a good teaching speaking during the lesson activity in class. to attract students’ attention during the lesson, the teacher should be smart in positioning himself in front of the students during the lesson activity, because the way of how teacher takes role during the class activity can also affect the students’ attention. One of the best methods in teaching English is Communicative Language Teaching. This method aims to make students can communicate through target language. Belchamber (2007) says that the main focus of CLT is to teach student use the target language as their media of communication. That is why this method is appropriate to support foreign language learners to communicate through the target language. There are lots of features that provide students to speak much use target language. CLT can be understood as the principles of teaching goal, all features in this method both the setting of the class, the role of teacher and also the class activities facilitate the learners well. One of the activities that is included in this method is Gap Information Activity. Harmer (2007) states that Information Gap is where two speakers have different bits of information and they can only complete the whole picture by sharing that information-because they have different information, there is a gap between them. It means that gap information is the class activity that is used to train students speaking skill communicatively. In this activity each student will be given a paper that consist different information with his partner. Students have to get the complete information by asking his partner. Harmer (2007) also says that the idea of information gap as an organizing concept for a speaking activity is that one person has information that another lacks. They must use English to share that information in order to accomplish a task. Through this activity student will get the real reason and situation that will make them communicate trough the target language In implementing gap information activity to teach speaking procedure text teacher needs to follow some steps that have been stated by Murray (2006) Pre Activity: This stage is the beginning of the lesson. Firstly, the teacher needs to tell students everything about the procedue text. Its aim, grammar features and also the generic structure. After that, teacher needs to tell the students the rules of the gap information activity. He also needs to show the students the example how they will do the gap information activity. Whilst Activity: This stage is the main activity of gap information. In this stage, teacher let students do the activity while the teacher himself watches his students and helps them with their difficulties. In this stage teacher should pay much attention to his students’ activity to make sure that the activity is going well. Post activity; This is the last stage of the lesson activity. In this stage teacher discuss the students’ work together. After that he tells the students the conclusion of the activity that they just did. Then he ends the lesson. It can be adapted from Ansarey (2012), her study by title “Communicative Language Teaching in EFL Contexts: Teachers Attitude and Perception in Bangladesh”. One of its aims is to find out the contribution of communicative language teaching in Bangladesh and the result of this study is it obviously shows that CLT can contribute much in helping develop more proficient speakers of English. METHODOLOGY Research Design The researcher used descriptive qualitative research design to obtain the information concerning with the implementation of gap information activity to teach speaking procedure to ninth graders. According to McMillan (1996) descriptive study investigates and describes the existing phenomena. It shows the real condition happens when the research is being conducted. The researcher is not allowed to manipulate anything, the condition of the research must be naturally happens. The researcher used descriptive research since the objective of this research was to demonstrate a class activity in teaching speaking procedure text. The researcher did not get involved in teaching and learning process. He only observed the teaching learning process in the class. The researcher did not make any interaction or participation during teaching and learning activity in class. The researcher only observed all activity that occurred during the lesson concerning how the teacher delivered gap information activity in teaching speaking procedure text. He kept on detail recorded of what happened and monitored the observation as the result. The researcher would only write what he saw and listened during the lesson activity. At the end of the observation, he would analyze the data involved observation checklist, field note and questionnaire. The Subject of the Study The subjects of the study were the ninth grade students. This research was conducted in class IX D of SMP Negeri 1 Bangkalan which consists of 36 students. Setting of the Study This study took place in the IX D class in SMP Negeri 1 Bangkalan.. The researcher chose SMP Negeri 1 Bangkalan as a place to conduct this study. The school was comfortable for learning activities since the school was surrounded by trees and the situation in the school was not too crowded, so that students could study pleasantly. Besides the students were also provided with facilities that supported teaching and learning activities, such as library and various laboratories, The important part of the school that encouraged the research to be successful was the clean, wide and comfortable classroom which the students were in to study. It was one of the essential facilities which give an effect for the teaching learning process. Those factors create conducive atmosphere in class the support the researcher to conduct this study. Moreover the teacher applies gap information activity that suitable with this study. Data and the Source of Data The data of the study were the activities in the teaching and learning process that were according to gap information activity. The researcher would describe the data in the form of words, phrases, and sentences, rather than numbers because the researcher would conduct the descriptive qualitative study. The data were in the form of description of the students' English oral performance during the gap information activity and the responses of the students. Those data were needed to answer research questions of the study. The data to answer the first research question “how is the implementation of gap information activity to teach speaking procedure to ninth graders?” were the class activity during the teaching and learning process. To get the data, the researcher use observation checklist to observe the presence of the behavior and field note to take a note of the thing that happened during the teaching and learning process. The data to answer the second research question “How is the students’ response of the implementation of gap information activity to teach speaking procedure text to ninth graders” were the students’ opinion. To get the data the researcher used questionnaire. Research Instrument Research instrument was an equipment to collect the data. In this study, the researcher would use observation checklist, field notes and questionnaire as instruments. Those would be explained below: Observation Checklist The researcher used observation checklist to understand individual behavior or process of occurring a noticeable activity in actual or situation. ”The simplest device used is a checklist, which presents a list of the behaviors that are to be observed. The observer then checked whether each behavior were present or absent” Ary, Jacobs, Sorensen, & Razavieh (2010). Through checklist the researcher would know which part of behavior was missed by teacher during lesson activity. Field Notes Field notes was a kind of brief notes made by the researcher to observe the teaching-learning process. The researcher used field notes to observe the activity in the class by watching, listening, paying attention and writing everything that could be used as the data during the research. Bodgan and Biklen (2003) say that field notes are the written account of what the researcher hears, sees, experiences and thinks in the course of collecting and reflecting on the data in the descriptive qualitative study. The researcher would write all the important things she would see, hear and some additional information that was not mentioned in the observation checklist. It is also supported by Wallace (1998) that making field notes can prevent the researcher from trouble and confusion in presenting data caused by continuing to the next things. It will help her to organize the data before the data is being analized. Questionnaire Questionnaire was an instrument to get the survey information from the research participants. It is in line with McLean in Cohen, Manion, & Morrison’s book ( 2007) state that questionnaire can be used to collect survey information that provide structure, often numerical data being able to administrated without the presence of the researcher and often being comparatively straight forward to analyzed. Data Collection Technique The researcher got the data from observation checklist, field note and questionnaire. The observation checklist was used to get the information during the teaching and learning process. The observation checklist was also to know whether the teacher applies the indicators or not. The field note would be used to records how teacher would implement gap information activity to teach speaking procedures text and what situation would occur during the lesson activity. It would be used by researcher to answer the first research question. To answer the second research question the researcher would use questionnaire. Questionnaire would gain the information about students' responses toward the implementation of gap information activity to teach speaking procedure text. Data Analysis Cohen, Manion, & Morrison (2007) state that data analysis of qualitative research is a process of categorization, description, and synthesis data in a form of participations’ definition. In analyzing the data, the researcher would present the result of the observation checklist, field note and questionnaire during three meetings. The results of observation checklist were analyzed based on the class condition and responses of the data students. The researcher would observe the teaching and learning process during three meetings. The results of the field notes are used to support and explore the data from the observation checklist and questionnaire. The results of the questionnaire are analyzed by dividing number of comments of each item with the total number of students then are multiplied with a hundred percent. RESULTS AND DISCUSSION Result The Result of the Observation Checklist and Field Note: Observation Day I The first observation was conducted on Wednesday, July 24th, 2013. It was Ramadan Month. Most of students who were Muslims were fasting that is why the learning activity in class was shorter than in regular days. It was 2 X 30 minutes for each meeting. The class was begun at 6.30 AM. Right at that time the observer together with all students entered the class. The observer took a seat at the back row in order to be able to take a note of the class situation during the class activity. The students were so crowded. They were so busy talking each other. At 6.35 AM the teacher came and asked all students to take their seat before the lesson began. In the very first time teacher asked one of the students to lead their praying before starting the lesson. This was the conversation that occurred in the beginning of the class: Dialogue I T : Halo guys, good morning S : Good morning sir, T : Ayo semuanya kembali ke tempat duduk masing2 yaa Ayo, rafa pimpin doa S : Before we start let’s pray together Than all students pray S : Finish! After praying, teacher checked the students’ attendance list by calling their names. At the beginning of the lesson, teacher reminded his students about the previous meeting. Their previous meeting was about reading procedural text. Teacher gave them short review about the previous meeting. Teacher asked students some questions about their previous meeting to stimulate students’ memory about previous material and to give them chance to speak when they answered the question. Dialogue II T : Ok students, know I want to check do you still remember about procedure text? S : Yes sir ( they answer in a choir) T : All right students, raise your hand please. (Some students raise their hands) Yes, andika please S : Procedure text is text tell we about doing and making pak T : Oh good, any other answer? Yana, please yana S : Same sir, text telling us to make or doing thing T : Yes, good. Procedure text is a text that tells us about doing or making something. Very good. What about the generic structure? Anybody knows? (Students answer in choir and the class become crowded) Teacher chose one students to answer his question S : Title, ingredients, steps T : All right good, the other? Teacher point other student S : Same with sir, the title, the tool and ingredients and the steps T : Ok, very good, it seems you understand about procedural text, jadi sekarang kita akan mulai ke speaking, apa speaking itu? S : Ngomong paaak ( together) In this point teacher had succeed to remind his students about the previous meeting’s material which was still related to today material. It also gives them chance to start speaking in answering some questions from the teacher which was as the warming up before they start to the main activity, speaking procedure. The next thing which was done by the teacher was telling his students about what they were going to do that day. Moreover teacher gave them example about their activity today. Teacher also asked his students to help him in doing the example of their main activity which was gap information activity. Dialogue III T : Oke anak anak, sekarang kita akan belajar speaking procedure text sambil main game, S : Horeee ( the class become crowded) T Nama gamenya adalah Gap Information. Dan dimainkan berdua dengan teman sebangku kalian yaa. Here I have the steps make instant noodle but it is not complete information it is only picture. Ayo latihan dulu sebelum main, mari kita lengkapi sama sama informasi how to make instant noodle Then the teacher sticks the incomplete text of how to make instant noodle to the whiteboard and ask the students to complete it together. T : OK, bangku sebelah sini, apa step number one? S : Masak airnya sir, T : Yes, come on in English please S : Boil the water T : Ok, good. Come on next row S : Keluarkan the noodle from its kemasan sir and then put in to the boiling water T : Ayo open your dictionary S : Take it of the package T : Ok, good, what’s next? S : Mix the flavor T : All right, and then? S : Mix the flavor with the noodle, and it’s ready to serve T : All right, you all are very good. Nah nanti kalian kerjakan sepert tadi ya, saling melengkapi dengan temen sebangku kalian masing-masing. Remember, always speak English because I will watch all of you. Ok students? S : yes sir After giving the students example about the activity, teacher gave his students the worksheet. The worksheet was a procedure text about how to serve a simple diner. Each student received a text with the same title but had different information. One student had the information which his bench friend did not have. The teacher asked them to complete their worksheet by asking to their bench friend. After that he walked around the class to watch and help his students. In the other side students were being so busy completing their worksheet. They did the gap information activity like what their teacher did. They asked their bench friend about the information they need to complete their worksheet. The conversation occured among the students during the main activity. They tried to speak English bravely and confidently to their friend. The atmosphere in the class was good enough and conducive that support students to speak English. Here are the examples of the students’ conversation. The examples of the conversation bellow were taken from several pairs of students in class: Dialogue IV S1 : What is the first ingredient? S2 : The first ingredient is water. S1 : OK, what is next? S2 : Akuuu. . . S1 : Oh,OK yes please. Dialogue V S3 : What is the second ingredient? S4 : The second ingredient is meatball S3 : Oke I get it. S4 : Next, what is the third? S3 : The ingredient number three is noodle S4 : Ok, its hamper lengkap S3 : What is next? S4 : Next ingredient is chili flavor. Now, what is the last ingredient? S3 : The last ingredient is salt. S4 : Ok, now it is complete. . Dialogue IV and dialogue V were the script of conversation that occurred from two different groups in the class during the activity of gap information. They participate very well and actively speak with their partners to complete the information of what ingredients they needed to serve a simple dinner. The similar conversation also occurred in the other pairs during the activity. They kept speaking actively during the gap information activity. The examples below were the conversation that occurred when some students were completing the steps of how to serve a simple diner. Dialogue VI S1 : The first step, Boil the water for ten minutes. S2 : Thank you S1 : Come on, next! S2 : Next is put in the meatball to the boiling water. Dialogue VII S1 : What is the step number three? S2 : Take the meatball, then put in the noodle to the water S1 : Ok, after that when the noodle masak, what is masak? S2 : Sir, masak bahasa inggrisnya apa sir? T : Just say being cooked, pake tobe ya. Is being cooked S1 : Thank you, Sir. Ok. When the noodle is being cooked put in the salt and mix it S2 : Ok, next step. Put in the chili flavor and mix it. S1 : Yes, after that put in the meatball and wait for three minutes. S2 : Then the food is ready. All students conducted the similar conversation with the examples above during the gap information activity. In the other side the teacher kept watching and guiding his students during the activity. The student centre activity like what happened in this class really gave much time to students to speak and express their English during the lesson. They did not need to be afraid of making mistake or asking because they had supporting environments to learn and practice to speak English. Besides, the teacher was always ready to help them if they had some difficulties or questions. After doing the gap information activity teacher asked all students to check their worksheet. At last teacher asked the students randomly to deliver the step how to serve a simple diner to the class. Teacher chose two students to speak in front of the class. Those lucky students are Suci and Ramdan. They did it well although grammatically they still made some mistake. In the end of class activity teacher asked his students to review what they had done that day. After that, the teacher asked students to make group of 6 that would be used in the next meeting. Teacher also gave students some assignment to find a procedural text for each group. And finaly teacher asked the captain of the class to lead his friends prayed before they went home. The Result of the Observation Checklist and Field Note: Observation Day II The observation day II was conducted on Friday, July 26th,2013. This observation was also conducted in 2 X 30 minutes. It was the same with the day I, the class also began at 6.30 AM. All students and the researcher entered the class right at 6.30 AM. Same with day I, the observer took seat in the back row in order to be able to watch the whole class. For about ten minutes after all students entered the class, teacher entered the class and greeted his students. After greeting and having little conversation with the students, he checked the attendance by calling the students’ name on by one. Next, he asked the students to sit with their group that they had made. After all students sit with their group, he asked the captain of the class to lead their friend prayed before starting the lesson. After that, teacher reviewed their previous meeting. The following was the dialogue between teacher and students in the beginning of the lesson. Dialogue VIII : T : Ok students, how are you all? S : Fine, Sir. T : Good, before we continue the lesson, I want all of you to sit with your group. S : (Students move to sit with their group) T : All right, good. Now before we start the lesson. Raffa, ayo pimpin doa S : Before we start, let’s pray together. (Everybody starts praying) Finish! T : Well students. now, I want to check. Who still remember about our class meeting (students answer in a choir, it makes the class crowded) T : Silent please, ayo dibiasakan raise your hand. Jangan keroyokan Yes, Lita please S : Learn about procedure text sir, play gap information how to serve simple dinner. T : Very good. Gitu dong, ngacung dulu kalo mau jawab. OK, now who still remember the generic structure of procedure text? Yes, anang, please S : The title, ingredients and steps sir. T : That’s good. I think You all still remember everything. Now it is time to submit your task. Ayo ketua kelompoknya maju kumpulkan tugas yang bapak kasih kemarin. This review was very useful as the warm up for the students before they continued to the main activity. Moreover, by remembering what they did in the previous meeting, it would make students be ready to receive material of the lesson that day. In this point, teacher also asked students some questions to make them speak, this was done to create English atmosphere in the class. However, when students had supporting environment they would participate well to the whole activity during the lesson. The next activity which was carried out by the teacher was another gap information activity. Different with the previous meeting, it was conducted in group not in pair. Students would do the activity with their group. It applied the basic concept of gap information activity where one of the group members had the information while the others did not have. Those who had the information should tell his friends what information he had to complete the worksheet was given by the teacher. Since the activity that day was different with the previous meeting. Teacher gave them example how to do the activity. He asked some students who were the representative from each group to come forward and help him gave an example to their friends. Before teacher started the example he stuck a passage of how to make meatball to the white board. After that all students who came forward was asked to gather as a group. Then he asked one of the members to read the text in the white board and remember it. Later when that students came back to the group he would tell the group what he had read and all members of the group will take a note of what their friend told them. Every single member of the group would have their own turn to read the passage and tell his group about the information that he read. In the end the group should collect all the information and complete the work sheet as the perfect procedure text. The dialogues bellow were some conversations that occurred when the teacher was giving the example. Dialogue IX : T : Well students, now we will do another gap information activity. S : Horeee ( students yelling together) T : We will do this activity in group. Does everybody have the group? S : Yes, Sir! T : Ok very good. I will give you example, but I need some students to help me. Ayo masing masing kelompok kirim satu orang untuk maju. How many groups is in here? S : Six groups, Sir T : OK. Sekarang bapak dan teman teman kalian akan memberi contoh bagaimana kita nanti akan melakukan gap informationnya. Well, here I have a passage of how to make meatballs. I will stick this passage to the whiteboard. Nah, sekarang. One of you read one sentence of this passage and tell your group. Come on do it. S : One student walks toward the whiteboard to read the text and then tell his friends what he just red. T : Nah sudah, gantian. Diikuti yang lain. Begitu seterusnya, urutan sampai teksnya selesai. Is it clear students? S : yes sir. After the example was given, the main activity, gap information, was started. On the white board there were three passages of procedure text. Text number one was how to make egg and lemon soup, text number two was how to make milkshake and text number three was how to make tomato soup. Group one and five were asked to do text number one, group two and four were asked to do text number two while group three and six got text number three. After listening to all instructions and getting their job, each group started doing the task. Every student was so busy completing the worksheet which had been given by the teacher. When completing the task some conversation occurred among students. The following dialogue was the example of conversation that occurred among students. Dialogue X S1 : The title is how to make egg and lemon soup. To make egg and lemon soup you need all these ingredients. (While one of the group member was saying the sentences, the other group members were taking note in their paper. Then after the first member finish, the next member immediately went to the whiteboard to get next information) S2 : Number one. Three pints chicken stock. Number two juices of two lemons. S3 : Number three salt and pepper. Number four, four eggs well beaten. The conversation above was the example of the dialogue when students in group one completing the ingredients of the procedure text. The similar conversation and situation also happened is the other group. The following was the dialogue of group six. Dialogue XI S1 : Number four, a half teaspoon of salt. Number five eight cups of water. S2 : Number six, one per four teaspoon of pepper. Number seven small clove of garlic S3 : The last ingredient is one pr four teaspoon of butter. In completing the next part of procedure text, the steps, students took longer time because the sentences were longer than in ingredients. However they still actively took part in the activity to complete their worksheet. The dialogue below was the example of conversation in group four when they were doing the steps of how to make milkshake. Dialogue XII S1 : Now follow these steps to make a milkshake S2 : Number one, place milkshake glasses into the freezer. S3 : Number two take the ice cream from the freezer before you. . . I forget, wait. (She went back to the whiteboard to read the text.) From the freezer before your shake. S4 : Number three, mix the ice cream, milk and added flavors into blender for one minute. S5 : Number four, pour shakes into the frosty glasses. Take the milkshake glasses out of the freezer, then pour the shake mixture in. S6 : Drop a straw into the shake, then enjoy The last thing that students needed to do after they had completed the ingredients and steps was collecting all those information and write it to the worksheet. Directly after it was completed, they submitted their worksheet to the teacher. In thirty minutes all groups had finished their work. Then, teacher asked one student of each groups to read their worksheet in front of the class. in the end of activity teacher asked the students to review what they had done that day. After that the captain of the class led their friend to pray. Before the class dismissed teacher greeted his students and the class was over. The Result of the Questionnaire The result of the questionnaire was used to find out the students’ responses during the implementation of gap information activity in teaching speaking procedure text. The questionnaire consisted of fourteen statements in the form of multiple choices. After classifying the result of the questionnaire, each opinion was calculated by dividing number of comments of each item with the total number of students then was multiplied with a hundred percent. The Students’ Opinion About the Teacher’s Role The result of the questionnaire showed that teacher really had good skill in teaching. More than seventy percent students said that they can easily follow his teaching way. Moreover most of students said that they understood what their teacher taught them. It was proved by more than seventy five percent students choose “understand” for the statement “do you understand what your teacher has taught you?”. Teacher also gave much time for students to take their role during the learning activity. More than eighty percent students said that teacher did not dominate the class activity. Most of students in that class also said that their teacher often gave them explanation for something they did not understand well. As well as more than eighty percent students agreed that their teacher also often asked them to deliver their idea or opinion during the class activity The Students’ Opinion About the Material Based on the sixth statement of the questionnaire, the text that was given by the teacher was quite easy to catch by students. More then half students in the class also agreed that the topic of the text was interesting enough for them. Moreover most of the students said that the material from the teacher increased their motivation to practice speaking English. However, students still found some difficult words in the text that was given by teacher as the material in during lesson activity. The Students’ Opinion About the Technique Students also gave their opinion relating with the activity conducted by the teacher. More than seventy percents of the students agreed that the activity was interesting for them. Teacher also gave quite clear explanation to the students about the procedure to do the activity. Most of the students also said that the activity increased their knowledge about the procedure text. They strongly agreed that gap information activity had motivated them well to speak English with their friend during the lesson. Moreover most of the students said that the activity was easy to do. Discussion The Implementation of Gap Information Activity to Teach Speaking Procedure Text to Ninth Graders In this chapter, the researcher would answer the first question of the research question. It was how the implementation of gap information activity to teach speaking procedure text to ninth graders is. The implementation of the gap information activity could be seen in the result of observation checklist and field note. In the first meeting the teacher began the meeting with reviewing their previous meeting. It was about the procedural text. The teacher explained about its generic structure and its aim. He also gave the example of the procedure text to the students. Afterward he explained to the students about the activity, gap information. Then, he continued giving them example how to do it. He asked the students to do the example together to stimulate them to speak as the warm up. After that he guided his students to conduct the main activity, gap information activity. In the first day, the activity of gap information was conducted in pair work. It was because the pair work was simple to do since the students had never done the gap information before. In the second day it was conducted in group work. The teacher let the students make the group of six by them self. During the main activity both in day I and day II the teacher walked around the class and kept his eyes on the students while the students were working with their partners. Sometimes he helped the students translating the difficult words. In the end of the lesson teacher asked some students to deliver their work in front of the class and discussed it together. The way of teacher conducted the lesson above showed that he gave much time to the students to practice their English. Klancar (2006) the opportunity of speaking will affect to the speaking ability. The more of speaking the learners get, the better they will become. The point was done during the teacher conduct the lesson. Before doing the main activity he gave students chance to speak while they were doing the example of gap information activity. Before, he also gave students chance to speak while reviewing the previous meeting. The gap information activity which was applied by teacher in class was suitable with Murray (2006). However, he modified the system according to the situation in the class. In the preparation the teacher preferred to make the worksheet by himself than collect the information from the students. The rest of the procedure was similar with what Murray suggested. He divided the students into small group (pair group in day I and bigger group in day II). Then he gave them the worksheet and asked them to complete the worksheet by trading the information they had with their friends. During the main activity, students actively spoke with their friends to complete the task. It was truly like what Harmer (2007) states that the idea of gap information activity as organizing concept for speaking is that one person has the information that another lacks. They have to speak English to share the information in order to accomplish the task. As the time ran out, he asked his students to deliver their work in front of the class. While a group was delivering their work, teacher was doing correction to it. Moreover the implementation of gap information activity really had helped teacher to attract students’ attention. It